The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.02.14.480333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical Control of Membrane Fluidity Modulates Protein Secretion

Abstract: The lipid composition of cellular membranes is dynamic and undergoes remodelling affecting biophysical properties, such as membrane fluidity, which are critical to biological function. Here, we introduce an optical approach to manipulate membrane fluidity based on exogenous synthetic fatty acid with an azobenzene photoswitch, termed FAAzo4. Cells rapidly incorporate FAAzo4 into phosphatidylcholine (PC), the major phospholipid in mammalian cells, in a concentration- and cell type-dependent manner. This generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Eukaryotic cells face the challenge of maintaining the properties of not just a single plasma membrane but that of several coexisting organellar membranes each with unique lipid compositions and each exchanging membrane material with other organelles via vesicular carriers and/or lipid transfer proteins. Despite recent advances to manipulate and follow membrane properties (John Peter et al , 2022; Renne et al , 2022; preprint: Jiménez-Rojo et al , 2022; preprint: Tsuchiya et al , 2022), we know little about how stressed cells coordinate membrane adaptation between organelles whilst maintaining organelle identity and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotic cells face the challenge of maintaining the properties of not just a single plasma membrane but that of several coexisting organellar membranes each with unique lipid compositions and each exchanging membrane material with other organelles via vesicular carriers and/or lipid transfer proteins. Despite recent advances to manipulate and follow membrane properties (John Peter et al , 2022; Renne et al , 2022; preprint: Jiménez-Rojo et al , 2022; preprint: Tsuchiya et al , 2022), we know little about how stressed cells coordinate membrane adaptation between organelles whilst maintaining organelle identity and functions.…”
Section: Introductionmentioning
confidence: 99%
“…12 These photolipids have been used to control biological targets of signaling lipids, including GPCRs, 13−15 ion channels, 16−18 enzymes, 19−22 nuclear hormone receptors, 23,24 and immunoreceptors, 25 and as a means to control membrane biophysics in model membranes 26−28 and cells. 29 However, to date, this approach has not been extended to other important classes of lipids, such as steroids or isoprenoids. The development of photoswitchable isoprenoid lipids was further motivated by previously reported arene-rich analogs that proved to be efficient substrates for FTase (Figure 1A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, this approach has been extensively explored for photoswitchable sphingolipids and glycerolipids . These photolipids have been used to control biological targets of signaling lipids, including GPCRs, ion channels, enzymes, nuclear hormone receptors, , and immunoreceptors, and as a means to control membrane biophysics in model membranes and cells . However, to date, this approach has not been extended to other important classes of lipids, such as steroids or isoprenoids.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, synthetic photoswitchable phospholipids, or photolipids, have emerged as a research tool to reversibly alter and control a variety of SLB properties, such as fluidity and thickness, lipid order and domain formation, protein molecular dynamics, and photoactivation of mechanosensitive channels by photoisomerization. Recent studies have further shown the potential of photolipids to trigger the release of molecular cargo from liposomes and lipid nanoparticles, and to control protein secretion in living cells by means of light …”
Section: Introductionmentioning
confidence: 99%